21st CENTURY QUESTIONS: THE STATE OF NIGERIA DEMOCRACY IN PERIL? VIOLENCE AND DEMOCRACY IN NIGERIA “MAPPING THE ROOTAGE” - Shaibu Sunday Danladi (European Scientific Journal, ESJ, 2013)
The growing violence and tension in Nigeria in the recent era demand scholastic exploration to explain the phenomenon and also it could be used to elucidate the ‘tap-Roots’ of the Nigeria states of violence, terrorism in a democratic dispensation its impacts on the nation stability. These studies examine the underlying root causes of violence, which has recently turned into the act of terrorism in Nigeria. Drawing from these indications, some literatures have indicated religious and protracted long competition among the three major regions in Nigeria as a unique index of the countries crises. Even so, The opening of this debate captures historical antecedent of what today is known as “Northern” Nigeria and had paid attention to various revolutionary traces of violence within the context of the Northern regions. The study interpreted the contemporary causes of violence, terrorism and other disturbance in Nigeria's geopolitics. Specifically, those which occurred in the form of political dissatisfaction among political parties that had recently gone beyond a border as violence intensified constantly. Consequently, given this greater danger to the nation unsettled domestic instability, higher tension in the country, these complexities' contradicts in contrast to the unpredictable and calm in Nigeria which had intensified the cause for this inquiry. Perhaps, It further accesses the dynamism and puzzles which fashioned out violence and act of terrorism from its original taproots of the nationhood. It argues that “Northern” Nigeria as regions does not in general produce terrorism but sufficiently traces identical “Bawa’s” dated back to the Kingdom of Northern Nigeria during Usman Dan Fodio 1903. It ﻿establishes that the spread of Islam and the growth of population as some act that erects some elements popularly refers as “sect” within the northern Nigeria. The result of this research revealed that the complexity and inequality which challenged the northern regions Nigeria historically attributed to the cost and effect of terrorism by the Islamic fundamentalist. It highlights literacy, political miscalculation, corruption, and external actors as factors that are reinforcing the prospect of the unstable democracy in Nigeria federation.